2007
DOI: 10.1258/095646207780749754
|View full text |Cite
|
Sign up to set email alerts
|

Are we missing mumps epididymo-orchitis?

Abstract: Mumps epididymo-orchitis has not been recorded as a cause of testicular symptoms without systemic features (including parotitis). The aim of the present study was to assess if we were missing cases in the genitourinary clinic during a previous outbreak of mumps in the community. During a prospective pilot study from November 2005 to February 2006, all patients presenting with symptoms or signs of epididymo-orchitis were studied. These patients were assessed for previous exposure to mumps virus or vaccine, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 3 publications
0
12
0
5
Order By: Relevance
“…Though epididymitis (inflammation of the epididymis) is more commonly caused by bacteria, viruses such as rubulavirus, coxsackie‐B virus, herpesvirus (HSV), and human papilloma virus (HPV) are likely viral pathogens in the epididymis (Dejucq & Jegou, ; Kapranos et al ., ; Emerson et al ., ; Vuorinen et al ., ). While investigating the antiviral defense response mechanisms of HEE cells (Browne et al ., ), we found that the toll‐like receptor (TLR) 3 and retinoic acid‐inducible gene I (RIG‐I)‐like receptors (RLRs) are enriched in cells from the corpus and cauda regions.…”
Section: Regional Distribution Of Antibacterial and Antiviral Responsmentioning
confidence: 99%
“…Though epididymitis (inflammation of the epididymis) is more commonly caused by bacteria, viruses such as rubulavirus, coxsackie‐B virus, herpesvirus (HSV), and human papilloma virus (HPV) are likely viral pathogens in the epididymis (Dejucq & Jegou, ; Kapranos et al ., ; Emerson et al ., ; Vuorinen et al ., ). While investigating the antiviral defense response mechanisms of HEE cells (Browne et al ., ), we found that the toll‐like receptor (TLR) 3 and retinoic acid‐inducible gene I (RIG‐I)‐like receptors (RLRs) are enriched in cells from the corpus and cauda regions.…”
Section: Regional Distribution Of Antibacterial and Antiviral Responsmentioning
confidence: 99%
“…Clinicians should be aware that orchitis may be secondary to mumps infection even in the absence of a history or clinical evidence of parotitis, as indicated by mumps‐specific serology (Philip et al. , 2006; Emerson et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…5 % der Patienten über einen respiratorischen Infekt innerhalb der letzten 10 Tage vor Beginn der Epididymitis [13,22]. Allerdings haben nur wenige Studien eine mögliche virale Genese untersucht [6,11,19,34,35]. In einer aktuellen Studie wurden alle Patienten ohne Nachweis bakterieller Erreger systematisch auf 23 verschiedene Viren mittels PCR-Diagnostik getestet.…”
Section: ) Virale Epididymitiden Sind Möglich Aber Seltenunclassified
“…In nur 2 Fällen wurden Enteroviren nachgewiesen, während Mumps trotz Diagnostik im nationalen Referenzzent-rum niemals detektiert wurde [13]. Obwohl das Mumpsvirus immer wieder in der Literatur als möglicher Erreger diskutiert wird [34], passen die Ergebnisse gut zu umfassenden epidemiologischen Daten von mehreren Tausend Fällen aus der Zeit vor Verfügbarkeit einer Vakzinierung, bei denen nach einer Parotitis primär der Hoden betroffen war und der Nebenhoden lediglich synchron oder metachron sekundär involviert war [36]. Der Nachweis von Viren im Ejakulat bzw.…”
Section: ) Virale Epididymitiden Sind Möglich Aber Seltenunclassified